Coping with psychotic-like experiences without receiving help from mental health care. A qualitative study. Issue 1 (2nd January 2017) - Boumans, Jenny; Baart, Ingrid; Widdershoven, Guy; Kroon, Hans
Abstract : This study describes the ways in which people with psychotic-like experiences without mental health care manage to achieve successful lives. The qualitative study, which used a grounded-theory approach combined with elements of narrative research, draws on interviews with 18 individuals who were recruited through a self-selection strategy via a national advertisement. The frequency of participants' psychotic-like symptoms was comparable to that of patients who receive mental health treatment for psychosis; however, participants experienced lower levels of distress. The results provide insight into the variety of strategies and interpretative frameworks participants develop to create and to maintain self-defined successful lives while coping with psychotic-like experiences. Experiential knowledge from people outside care settings can be helpful in the development of more sophisticated activities, ideas, and discussions within the international recovery movement.